Thematic Working Group 15. Teaching mathematics with technology and resources - CLARK-WILSON, Alison Margaret; Robutti O.; Turgut M.; Kohanová I. (Freudenthal Group & Freudenthal Institute, Utrecht University and ERME, 2019)
At CERME11 two groups addressed mathematics education research concerning technology. TWG15 focused on issues related to teaching, teacher education and professional development, whereas TWG16 focused on students’ learning with technologies, alongside software and task design issues (see Introduction to TWG16 in this volume). The TWG15 work was stimulated by contributions in the form of 12 research papers and 8 posters that had responded to the call that had highlighted the following themes: • The specific knowledge, skills and attributes required for efficient/effective/equitable mathematics teaching with generic and mathematics-specific technologies and resources. • The design and evaluation of initial teacher education and teacher professional development programmes (to include MOOCs) that embed the above knowledge, skills and attributes. • Theoretical and methodological approaches to describe the identification/evolution of teachers’ practices (and of ‘best’ practices) in the design and use of technology and resources. • Theory and practice relating to the formative/summative assessment of mathematical knowledge in technological environments. The work of TWG15 drew upon research from 13 countries: Austria, Brazil, Denmark, England, France, Iceland, Israel, Germany, Greece, Norway, Portugal, Sweden and Turkey.